Pengaruh Investasi Publik dalam Sektor Kesehatan, Pendidikan, dan Infrastruktur terhadap Pertumbuhan Ekonomi Indonesia : Analisis ARDL Tahun 2002-2023 - Nurfadia, Atikah; Nurkarim, Wahidya (Seminar Nasional Official Statistics, 2025)
Indonesia's Gross Domestic Product (GDP) has steadily increased in the past two decades to reach US$1.4 trillion. This growth is driven by various factors including domestic consumption, investment, and labor. This study aims to analyze the impact of government spending in the health, education, and gross fixed capital formation sectors on Indonesia's economic growth. Annual data from 2002 to 2023 were analyzed using the Autoregressive Distributed Lag (ARDL) approach to examine both short-term and long-term relationships among the variables. The results show that, in the long run, health expenditure and gross fixed capital formation have a positive and significant effect on gross domestic product (GDP) per capita. Conversely, education expenditure exhibits a negative and statistically insignificant effect. In the short run, only health expenditure has a significant influence on economic growth. Diagnostic tests indicate that the ARDL model used satisfies statistical assumptions and is structurally stable. These findings highlight the importance of optimizing education spending and maintaining as well as enhancing investments in the health and infrastructure sectors to support sustainable economic growth.